Perancangan Interior Coffee Edu-Tourism Centre Di Kebun Kopi Karanganyar - Elizabeth Elizabeth; Lintu Tulistyantoro (Intra, 2019)
The expansion of coffee industry in Indonesia makes coffee becomes a part of lifestyle for most people. Indonesian coffee has managed to be popular to foreign countries and that makes Indonesia is also well-known in the world. Therefore, the Indonesians need to know, explore and love their own local products.The purpose of this Interior Design is in order to know more about Indonesian coffees, people needed the information about types, history, the culture of coffee, how to process coffee, and the needs for facilities that provides experiences to explore and enjoy coffee in full with attractive interior ambients, that can be obtained through structuring design elements based on the art and design knowledges. The facilities includes the form of cafes, coffee workshops, information on coffee galleries, and coffee stores, by displaying a comfortable and pleasant interior atmosphere, to attract local and foreign tourists in the world of coffee, especially Indonesia’s local.